2004
DOI: 10.1023/b:ddas.0000043371.12671.98
|View full text |Cite
|
Sign up to set email alerts
|

The Adherent Gastric Mucous Layer Is Composed of Alternating Layers of MUC5AC and MUC6 Mucin Proteins

Abstract: Mucin-type glycoproteins are the major structural proteins in gastric mucus. Stomach mucin proteins include MUC5AC, synthesized by surface foveolar or pit cells, and MUC6, synthesized by neck and gland cells. The aim of this study was to determine the spatial distribution of these mucin proteins within the extracellular mucous coat. Double-labeling immunoflourescence/confocal microscopy was used in histologically normal surgical resection specimens. Intralumenal mucin within antral glands consisted entirely of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 21 publications
5
56
1
2
Order By: Relevance
“…MUC5AC is expressed in the surface mucus cells and MUC6 by the mucus neck cells in the gastric glands (26,34). Immunohistochemistry of human biopsies have revealed that the adherent mucus layer contains segregated MUC5AC and MUC6 mucins, which are arranged in a laminated linear way, with a continuous sheet of MUC5AC mucins immediately adjacent to the surface epithelium (13). MUC6 mucins are found in thinner, more truncated layers interspersed in the MUC5AC mucus layer.…”
Section: Discussionmentioning
confidence: 99%
“…MUC5AC is expressed in the surface mucus cells and MUC6 by the mucus neck cells in the gastric glands (26,34). Immunohistochemistry of human biopsies have revealed that the adherent mucus layer contains segregated MUC5AC and MUC6 mucins, which are arranged in a laminated linear way, with a continuous sheet of MUC5AC mucins immediately adjacent to the surface epithelium (13). MUC6 mucins are found in thinner, more truncated layers interspersed in the MUC5AC mucus layer.…”
Section: Discussionmentioning
confidence: 99%
“…Mucins secreted from these mucous cells form the surface mucous gel layer (SMGL) covering the luminal surface of the gastric mucosa [2]. The SMGL shows a laminated structure consisting of mucous layers of the SMC-type mucin and those of the GMC-type mucin [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…However, mucin production is typically a protective response against bacterial infection, and therefore, it may be exploited by the CagA protein (31)(32)(33). MUC5AC, as a principal component of the mucosal layer, protects the stomach surface from chemical, enzymatic, mechanical and microbial challenge, and its upregulation constitutes an intuitive response of the epithelium to infection (1,2,7,11,29,(34)(35)(36). Additional studies are required to delineate the molecular mechanisms, which mediate the effects of CagA on MUC5AC transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Mucin 5AC oligomeric muscus/gel-forming (MUC5AC) is a principal component of the gastric mucosa (1,2) and constitutes an important part of the ecological niche, where the stomach bacterium Helicobacter pylori is located (3). Adhesion to the gastric mucosa is important in the life cycle of H. pylori (4).…”
Section: Introductionmentioning
confidence: 99%